Autologous US-guided PRP injection versus US-guided focal extracorporeal shock wave therapy for chronic lateral epicondylitis: A minimum of 2-year follow-up retrospective comparative study. (11th January 2018) - Alessio-Mazzola, Mattia; Repetto, Ilaria; Biti, Besmir; Trentini, Roberto; Formica, Matteo; Felli, Lamberto
Purpose: To compare the efficacy of two independent groups of patients treated with ultrasound (US)-guided extracorporeal shock wave (ESW) therapy and with US-guided injection of platelet-rich plasma (PRP) for chronic lateral epicondylitis (LE) with a minimum of 2-year follow-up. Methods: We retrospectively evaluated 63 patients treated for chronic LE (31 patients with autologous US-guided PRP injection and 32 patients with US-guided focal ESW therapy) from 2009 to 2014. All the patients were evaluated by means of Roles–Maudsley (RM) score, quick Disabilities of Arm, Shoulder, and Hand (QuickDASH) score, visual analogic scale (VAS) and patient-rated tennis elbow evaluation (PRTEE) to retrospectively assess the pain relief, level of activity, the self-reported function and subjective satisfaction at minimum of 2-year follow-up. Results: Both US-guided autologous PRP injection and US-guided focal ESW administration proved effective in chronic LE with significant improvement in the QuickDASH, VAS, RM and PRTEE scores ( p < 0.0001). No adverse effects or complications were recorded in any groups. No differences were found in recurrence rate and final results of the QuickDASH, VAS, RM and PRTEE scores between the two groups ( p > 0.05). The mean time between treatment and symptom resolution was significantly shorter for the PRP treatment ( p = 0.0212); furthermore, the mean time to return to the normal activities was quicker for PRP group ( p = 0.0119). Conclusion: Both PRP injection and ESW therapy are feasible and safe options for the treatment of chronic LE with low risk of complications and with good long-term follow-up results. US-guided PRP injection has quick efficacy when compared with US-guided focal ESW therapy.